Xenobiotic gene polymorphisms and susceptibility to multiple myeloma - LF Lincz; I Kerridge; FE Scorgie; M Bailey; A Enno; A Spencer (Haematologica, 2004)
Genetic variations in the activity of xenobiotic enzymes may predict susceptibility to multiple myeloma (MM). In a case-control study, 90 Australian Caucasians with MM had significantly higher incidences of GST T1 null, PON1 BB and NAT2 slow acetylation genotypes, but no difference in polymorphism frequencies for GST M1, NAT1, and CYP1A1 when compared to 205 controls.